Local Wisdom Approach in Creating Comfort for the Children of the Orphanage on Bunga Ncole Street Medan - Hillery Milenia Ginting; Firman Eddy (International Journal of Architecture and Urbanism, 2023)
Architecture is a field that overcoming growth and development of children's Orphanage, one of which is by creating comfort and safety for foster children through architectural design and the available facilities. This journal aims to find out how the local wisdom approaches can correlate with the design of an orphanage so that it can create comfort for foster children or the local community. This journal uses a qualitative method consisting of secondary data, including literature studies and primary data (location surveys and observations, and interviews). After the data has been collected, then data analysis is carried out so as to be able to explain the results and conclusions of the study. The local wisdom approach considers important regulations and information that apply in the location that is the object of research. The local wisdom approach includes aspects of climate, culture, society, and existing habits so that the child orphanage is able to provide comfort and security for the orphanage children in their growth, study and work so that it is beneficial for their future. Through writing this journal, it is known that the Local Wisdom Approach at the research location is able to have a good correlation between the design of the Orphanage with the supporting aspects of the local area, as well as providing comfort for the Orphanage children and having a positive impact on the surrounding community.